Integrating multicultural perspectives in language teaching - Muhamad, Ainon Jariah; Esa, Zaleha; Abdul Malik, Faridah; Engku Ibrahim, Engku Haliza (2015)
An important aim of international institutions of higher education is to promote positive interactions and intercultural awareness on their campuses, especially those institutions hosting large numbers of international students. These institutions should work towards developing skills that would enable staff and students to become interculturally competent to live, study and work in an international context. The objective of this study is thus to investigate the multicultural practices of academic staff in an institution of higher learning in Malaysia which caters to a very culturally diverse population of students. With internationalization and integration as two of the important missions of the institution it is only appropriate that this study be carried out as it is crucial for teachers to examine their own knowledge and teaching behavior, the values, as well as perspectives of the cultural groups who are the subjects of their teaching, and be able to transfer that knowledge into effective instruction. Data collected will be based on the responses of questionnaires distributed to 40 language teachers. Findings of the study would provide an insight into the extent of teachers’ multicultural practices, crucial in contributing towards actualizing the vision and mission of the university.